Perempuan dan Kekerasan - Merlia Indah Prastiwi (DIMENSI - Journal of Sociology, 2016)
Violence often occurs in women, both within the family and the social sphere. Violence not only physically, but also non-physical harm self-esteem and dignity of women. Why is a weak creature is always subordinate? Madura with kepatriarkhiannya trying to protect women with housing concept tanean lanjeng. On the other hand male ownership of women in Madura makes man superior to violence against women, especially within families is commonplace. Blow-upof the existing problems in the household has become a taboo that most of the wives of their mouth shut and live the life that God gives. Among many such women, there are some women who could untu boost the courage to say stop theviolence.